A unique case of a newborn with a hemangioma on the omphalocele sac - Erten, Elif Emel; Azılı, Müjdem Nur; Güney, Doğuş; Demir, Sabri; Ertürk, Ahmet; Öcal, Medine Ezgi; Demir, Tuğba Örnek; Bostancı, Süleyman Arif; Öztorun, Can İhsan; Şenel, Emrah (The Turkish Journal of Pediatrics, 2022)
Background. Mass lesions of the umbilical cord are rare anomalies. There have been rare reports of hemangiomas of the umbilical cord, but the co-occurrence of omphalocele and hemangioma of the umbilical cord has not been previously reported. Nonetheless, the condition is clinically significant as it may cause the disturbance of intrauterine fetal circulation, retardation of fetal growth and development, non-immune hydrops fetalis, morbidity and mortality. Case. Here we aim to report a case that was prenatally diagnosed with an omphalocele and that presented after birth with a hemangioma on the omphalocele sac. Conclusions. When dealing with umbilical mass lesions in the prenatal and postnatal periods, a hemangioma on the omphalocele sac should be considered in the differential diagnosis of patients when an omphalocele is suspected.
Keywords: hemangioma; newborn; omphalocele